Praktik Massompek Sebagai Prinsip Penyebaran dan Ketahanan Diaspora Bugis di Wilayah Maritim Indonesia-Malaysia - Afdhal Faizur Ridho; Imam Fadhil Nugraha (Student Research Journal, 2024)
Indonesia is the world's largest archipelago with a diversity of cultures that enrich its national identity. Among these cultures, the Bugis culture of South Sulawesi stands out for its rich traditions and deep maritime heritage. One of the major practice in Bugis identity is massompek, a centuries-old migration practice that reflects the Bugis ethos of resilience, self-reliance, courage and the search for a better life. Massompek brought Bugis communities to form influential diaspora networks in Indonesia and internationally, particularly in Malaysia. These diaspora communities contribute greatly to the local economy and trade, building strong social networks and encouraging cultural exchanges that reinforce their collective identity. This article examines massompek as a dynamic force shaping the Bugis diaspora, focusing on its cultural, economic and social impact in Malaysia. It also discusses the challenges of modernization and cultural preservation faced by younger generations of the Bugis diaspora and considers the role of the Indonesian and Malaysian governments in supporting the sustainability and integration of Bugis heritage through targeted cultural and economic initiatives.